2004
DOI: 10.1039/b312145n
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-based heterogeneous catalysts for Suzuki and Heck reactions

Abstract: Novel supported palladium catalysts have been developed based on chitosan as a support. These catalysts display excellent activity in the Suzuki and Heck reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(129 citation statements)
references
References 25 publications
2
122
0
5
Order By: Relevance
“…These ligands can be easily synthesized by the condensation reactions between pyridine-2-carboxylaldehyde and different diamines. This simple synthetic approach means that the ligand synthesis is amenable to forming heterogeneous solid-supported catalytic systems [52]. In our study, the resulting ligands contain backbones of differing chemical type and length attached to the donor groups.…”
Section: Ligand Effectmentioning
confidence: 99%
“…These ligands can be easily synthesized by the condensation reactions between pyridine-2-carboxylaldehyde and different diamines. This simple synthetic approach means that the ligand synthesis is amenable to forming heterogeneous solid-supported catalytic systems [52]. In our study, the resulting ligands contain backbones of differing chemical type and length attached to the donor groups.…”
Section: Ligand Effectmentioning
confidence: 99%
“…Also in 2004, Macquarrie et al 205 prepared the chitosanpyridine imine-based palladium complex 120 ( Figure 20) and found that it is an excellent and reusable precatalyst for Suzuki reactions involving aryl and heteroaryl bromides.…”
Section: Figure 17mentioning
confidence: 99%
“…Immobilization of catalysts on polymer supports also improves catalyst recyclability and performance. Progress has been made in using polymer supports based on natural resources; for example, chemically modified chitosan films have been used to support catalysts for Suzuki and Heck reactions (31), and materials made from corn starch show promise in heterogeneous base catalysis (32).…”
Section: Catalysismentioning
confidence: 99%